Beyond tokenism, toward resilience: furthering a paradigmatic shift from intersecting narratives of disaster and disability realities in East Java, Indonesia - Erna Setijaningrum; Asiyah Kassim; Agie Nugroho Soegiono; Putu Aditya Ferdian Ariawantara (Cogent Social Sciences, 2024)
The often-neglected intersection between disaster and disability in disaster management initiatives perpetuates a disproportionate impact on people with disabilities, reinforcing existing barriers and eroding overall resilience. Through an exploration of personal perspectives among 17 people with socially determined, self-identified disabilities amidst Indonesia’s disaster landscapes, we seek insights on amplified risks but also resilience pathways carved through cumulative exposures. Despite infrastructure barriers exacerbating disaster anxieties, there was resilience exhibited by people supporting one another through wisdom gained from repeated exposures, thus countering their exclusion. Findings also reveal societal forces sustaining unequal marginalization through stigma, yet unexpectedly cultivating solidarity as disability groups unite amid crises. Herein lies an appeal to leverage currently overlooked capabilities by meaningfully engaging disabled experts with lived experience navigating exclusion to guide context-driven strategies that fill gaps when systems fall short. We thus respond to calls for inclusive paradigms championing priority-setting participation of people with disabilities in directing equitable resilience initiatives benefitting all. Looking ahead, at the intersection of disability and disaster, the stage is set for more participatory efforts that embed disabled individuals as leaders to champion inclusion and social justice in the face of intensifying risks as more equitable communities are built.